Diagnosis and management of drug‐induced anaphylaxis in children: An EAACI position paper. Issue 3 (29th April 2019) - Atanaskovic‐Markovic, Marina; Gomes, Eva; Cernadas, Josefina Rodrigues; du Toit, George; Kidon, Mona; Kuyucu, Semanur; Mori, Francesca; Ponvert, Claude; Terreehorst, Ingrid; Caubet, Jean‐Christoph
Abstract: Drug hypersensitivity reactions (DHR) constitute a major and common public health problem, particularly in children. One of the most severe manifestations of DHR is anaphylaxis, which might be associated with a life‐threatening risk. During those past decades, anaphylaxis has received particularly a lot of attention and international consensus guidelines have been recently published. Whilst drug‐induced anaphylaxis is more commonly reported in adulthood, less is known about the role of drugs in pediatric anaphylaxis. Betalactam antibiotics and non‐steroidal anti‐inflammatory drugs are the most commonly involved drugs, probably related to high prescription rates. Diagnosis relies on the recognition of symptoms pattern and is based on complete allergic workup, particularly including skin tests and/or specific IgE. However, the real diagnostic value of those tests to diagnose immediate reactions in children remains not well defined for a significant number of the drugs. Generally, a drug provocation test is discussed to confirm or exclude an immediate‐onset drug‐induced hypersensitivity. Although avoidance of the incriminated drug (and related drug) is the rule, rapid desensitization is useful in selected subgroups of patients. There is a need for large, multicentric studies, to evaluate the real diagnostic value of the currently available skin tests. Moreover there is also a need to develop new diagnostic tests in the future to improve the management of these children. Abstract :